Inhibition of neuronal necroptosis via disruption of RIPK1-RIPK3 Interactions: The role of neural stem cell-derived exosomes in spinal cord injury recovery - Shiming Li; Guoliang Chen; Kuileung Tong; Yunshu Che; Yifan Xie; Wenxiao Shi; Anquan Huang; Yefeng Wang; Jianfeng Li; Genlong Jiao; Dacheng He; Jun Shen; et al. (Bioactive Materials)
Spinal cord injury (SCI) poses a significant economic and public health burden. Exosomes derived from neural stem cells (NSC-Exos) are emerging as a promising therapeutic strategy for SCI repair, overcoming several limitations associated with both autologous and allogeneic neural stem cell therapies. This study demonstrates that NSC-Exos are efficiently internalized by the injured spinal cord after co-injection, resulting in substantial motor function recovery in murine models. Additionally, NSC-Exos effectively limit the expansion of the injury site, reduce neuronal degeneration, and attenuate neuroinflammatory responses. Notably, this is the first study to identify necroptosis as a novel therapeutic target for NSC-Exos in SCI recovery. We show that NSC-Exos inhibit neuronal necroptosis both in vivo and in vitro by disrupting the RIPK1-RIPK3 interaction, thereby preventing necrosome assembly. Furthermore, comprehensive transcriptomic analysis reveals that the ubiquitin-mediated proteolysis (UPS) pathway plays a crucial role in this process, a finding supported by experimental inhibition of ubiquitination. In conclusion, this study highlights the therapeutic potential of NSC-Exos in SCI treatment, particularly through the inhibition of necroptosis via disruption of the RIPK1-RIPK3 interaction, potentially involving UPS activation. These findings provide a foundation for future investigations into the molecular mechanisms underlying SCI recovery.